Physico-microbial investigation of mango (cv. Amrapali) under non-chemical preservation - Hafiz, MMH; Hossain, MM; Karim, MR (Progressive Agriculture, 2018)
Enormous postharvest losses occur in mango at different points of postharvest storage in Bangladesh. Various detrimental chemicals are used in most cases to prevent the postharvest loss. Thus, non-chemical storage strategy has become a crying need to prevent the use of hazardous chemicals. So, this experiment was carried out on mango cv. Amrapalihaving five non-chemical postharvest treatments viz., Control, Perforated polyethylene bag, Unperforated polyethylene bag, Chitosan coating & Edible oil (soybean) coating under two storage conditions viz., Ambient condition & Refrigerated condition to point out suitable storage approach through the assessment of physico-microbialattributes. The experiment was laid out in a completely randomized design with three replications. Parameters investigated were total weight loss, peel colour, firmness, visual & other characteristics, disease incidence and disease severity. The results revealed significant influence on all the parameters by both of the factors. At 9 days after storage (DAS), minimum weight loss (1.56%) was recorded at unperforated polyethylene bag under refrigerated condition but maximum weight loss (17.08%) was in control under ambient condition. The perforated polyethylene bag under refrigerated condition showed the lowest peel colour score (1.00) at 9 DAS which give the hint of longer storage. The scores of firmness change were also the lowest in unperforated (1.00) and perforated polyethylene bag (1.05) at 9 DAS, respectively. There was no disease incidence and severity in any of the treatments under refrigerated condition whereas 100% disease incidence was noticed in the control under ambient condition at 9 DAS. At later stages of storage, off-flavor was developed in unperforated polyethylene bag due to anaerobic respiration. The fresh and edible pulp without any off-flavor was recorded up to 27 DAS in perforated polyethylene bag under refrigerated condition. Hence, the perforated polyethylene bag under refrigerated condition could be a promising storage strategy for mango. Progressive Agriculture 29 (3): 221-232, 2018